2006
DOI: 10.1007/s00213-006-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing effects of methylenedioxy amphetamine congeners in rhesus monkeys: are intravenous self-administration experiments relevant to MDMA neurotoxicity?

Abstract: Rationale: Many animal models relevant to the persistent effects of drugs of abuse necessitate the application of interspecies dose scaling procedures to approximate drug administration regimens in humans, but drug self-administration procedures differ in that they allow animal subjects to control their own drug intake. Objectives: This report reviews the reinforcing effects of 3,4-methylenedioxymethamphetamine (MDMA), its enantiomers, and several structural analogs in rhesus monkeys, paying particular attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 90 publications
2
22
0
Order By: Relevance
“…This finding is consistent with previous reports from studies with rats (Ratzenboeck et al 2001;Schenk et al 2003), rhesus monkeys (Beardsley et al 1986;Fantegrossi et al 2002;Fantegrossi 2006;Lile et al 2005) and baboons (Lamb and Griffiths 1987), and with the well-established abuse liability of MDMA (Strote et al 2002;Yacoubian 2003). The study by Lile et al (2005) used a PR schedule similar to the one used in the present study, but with a different progression in response requirement and a shorter TO between injections.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous reports from studies with rats (Ratzenboeck et al 2001;Schenk et al 2003), rhesus monkeys (Beardsley et al 1986;Fantegrossi et al 2002;Fantegrossi 2006;Lile et al 2005) and baboons (Lamb and Griffiths 1987), and with the well-established abuse liability of MDMA (Strote et al 2002;Yacoubian 2003). The study by Lile et al (2005) used a PR schedule similar to the one used in the present study, but with a different progression in response requirement and a shorter TO between injections.…”
Section: Discussionsupporting
confidence: 92%
“…The blunted responsiveness to MDMA shown here agrees with previous reports of tolerance to diverse effects of MDMA in rats, including anorexia (Zacny et al, 1990), discriminative stimulus properties (Schechter, 1991, Virden andBaker, 1999), hyperthermia (Shankaran andGudelsky, 1999, Piper et al, 2006) and locomotor activity Geyer, 1992, Brennan andSchenk, 2006). Tolerance to behavioral actions of MDMA is also well documented in non-human primates (Frederick et al, 1995, Frederick and Paule, 1997, Fantegrossi et al, 2004, Fantegrossi, 2007. On the other hand, a number of studies in rodents provide evidence for sensitized responsiveness after repeated MDMA exposure (Poland et al, 1997, Kalivas et al, 1998, Giorgi et al, 2005, suggesting tolerance development is not a universal outcome.…”
Section: Discussionsupporting
confidence: 90%
“…Tolerance to behavioral actions of MDMA is also well documented in non-human primates (Frederick et al, 1995, Frederick and Paule, 1997, Fantegrossi et al, 2004, Fantegrossi, 2007. On the other hand, a number of studies in rodents provide evidence for sensitized responsiveness after repeated MDMA exposure (Poland et al, 1997, Kalivas et al, 1998, Giorgi et al, 2005, suggesting tolerance development is not a universal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used variants of allometric scaling to equilibrate the doses of MDMA administered to experimental animals to human consumption (Mueller et al, 2008). However, these allometric models are sensitive to the pharmacokinetic and corrective factors used and can thus yield highly variable estimates (Yates and Kugler, 1986;Baumann et al, 2007;Fantegrossi, 2007). Furthermore, previous studies have shown that the doses of MDMA voluntarily self-administered by rhesus monkeys (Fantegrossi et al, 2002;Banks et al, 2008) are within the range, on a mg/kg basis, that humans abuse (1-2 mg/kg) (Cole et al, 2002;Harris et al, 2002;Green et al, 2003).…”
Section: Effects Of S(ϩ)-mdma (F) Sr(ϯ)-mdma (‚) and R(ϫ)-mdmamentioning
confidence: 99%